No rules rules Netflix and the culture of reinvention - Hatings, Reed. (London Virgin Digital, 2020)
These are some of the ground rules if you work at Netflix. They are part of a unique cultural experiment that explains how the company has transformed itself at lightning speed from a DVD mail order service into a streaming superpower - with 190 million fervent subscribers and a market capitalisation that rivals the likes of Disney.
Includes index
Keywords: Netflix (Firm); Internet television; Streaming video; Success in business